KESADARAN HERMENEUTIK DALAM MEMBACA TEKS: MODEL IJTIHAD UMAR IBN AL-KHATTAB - Alma`arif Alma`arif (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2016)
Umar ibn al-Khattab was one of the most controversial caliphs. He was a caliph that was courageous or "disobedient" to the text of Alqur’an and Sunnah literally. This “disobedient”side of Umar ibn al-Khattab brought up a serious reaction from the other companions. Toward this context, Umar ibn al-Khattab could be said as the “liberal” companion, because of his courage to re-interpret the sacred text. From the J.E. Gracia’s perspective, the way of Umar ibn al-Khattab interpreting the sacred text is a sophisticated reading, considering that at the time he had already been aware of the hermeneutic difference from other companions. This hermeneutic consciousness was able to make Umar bin al-Khattab placing the sacred text as a text that can be reinterpreted in accordance with the certain conditions and its maqasid can be taken. Thus, the sacred text revealed historically, is always sahih li kulli zaman wa makan.